Knowledge Representation and Management: Notable Contributions in 2021 - Cui, Licong; Dhombres, Ferdinand; Charlet, Jean (Yearbook of Medical Informatics, 2022)
Objectives: To select, present, and summarize the best papers in the field of Knowledge Representation and Management (KRM) published in 2021.Methods: Following the International Medical Informatics Association (IMIA) Yearbook guidelines, a comprehensive and standardized review of the biomedical informatics literature was performed to select the best KRM papers published in 2021, based on PubMed queries.Results: A total of 1,231 publications were retrieved from PubMed. We nominated 15 candidate best papers, and four of them were finally selected as the best papers in the KRM section. The topics covered by these papers include knowledge graph, ontology development, ontology alignment, and the International Classification of Diseases.Conclusion: In the KRM best paper selection for 2021, the candidate best papers covered a wider spectrum of topics compared to the last year’s significant focus on ontology curation. In particular, ontology development for specific domains (e.g., Alzheimer’s disease, infectious diseases, bioethics) has received the most attention.
Keywords: Knowledge representation and management; ontology; KnowledgeGgraph; International Medical Informatics Association